Effect of cross sectional shape on the energy absorbing characteristics of a tube under quasi-static loading - Syed Mohamed Ali, Jaffar; Abdullah, Kassim Abdulrahman; Aminanda, Yulfian (Trans Tech Publications Ltd., Switzerland, 2013)
In this study, numerical simulation of tubes of various cross section under axial compression is carried out using LS-DYNA. The effect of varying configurations of tube crosssection shape on the deformation response, collapse mode and energy absorption characteristics of tubes under quasi-static axial compression have been studied. The validation of the finite element tube model was made by comparison with the experimental results of the square tube subjected to quasi-static axial compression. Tabulated results are presented and plots have been included for the specific energy absorption for different cross sections. The study provides an insight on ways to increasing energy absorption of light weight aluminium tubes.